Wacana Pemerintah Untuk Mereposisi Kelembagaan Inspektorat: Tindak Lanjut, Tanggapan, Serta Inisiasi Kedepan - Wibowo, Richo A.; Yuniza, Mailinda E.; Widyaningtyas, Rizky S.; Noor, Hendry Julian (Jurnal Hukum & Pembangunan, 2018)
This research aims (i) to elaborate about a central government plan on repositioning the structure of inspectorate; (ii) to explain responses of some inspectorate officers regarding the plan; and (iii) to provide suggestions on the adjustment plan that should be taken into consideration by the central government. This research found that, different with the public perception, the plan is not intended to reposition all the inspectorates, rather to inspectorates attached to local governments. These inspectorates are designed to be what the-called ‘kuasi vertical institution’. Meaning, it has a mixed character of both central and local government institution. This initiation increases the the echelon of the the head of local insepectorate and influences the relation between local inspectorate and head of local government. Officers who pros with this plan believe that this will enhance their independency (nb. we believe that the used term suppose to be impartiality); therefore, they will be more immune from the intervention.